Validação semântica e psicométrica do banco de itens destreza manual do PROMIS® pediátrico para a população brasileira - Marques, Rafaela do Nascimento Borges Marques (2018)
Background: The Patient-Reported Outcomes Measurement Information System (PROMIS®) is a set of person-centered measures composed of several Item Banks that evaluates and monitors physical, mental, and social health in adults and children. In the Pediatric field (8 to 17 years) of the Physical Function is the Upper Extremity Item Bank, which investigates the coordinated functioning of the upper extremity in daily life activities. The availability of the version for use in Brazil is necessary for later use in the CAT (Computer Adaptive tests) and to contribute with practices and clinical research. Objective: Translate, cross-culturally adapt and validate the Pediatric Upper Extremity Item Bank of the PROMIS for the brazilian population. Method: Qualitative and quantitative study in the following stages: (1) Translation and cross-cultural adaptation and (2) Validation of psychometric properties. (1) According to the PROMIS recommendation, a translation followed for the Assessment Methodology of Chronic Disease Therapy (FACIT). A pre-final version was tested with 10 participants, who participated in a focus group with content analysis and two interviews, a cognitive and a retrospective clarification, for semantic validation. (2) A final version of the translation, composed of 31 items, was self-administered by 400 children with different health conditions. Data Quality, reliability and performed by Confirmatory Factor Analysis (CFA) and Exploratory Factor Analysis (EFA) for calibration were evaluated of the items by the Item Response Theory (TRI), through the Samejima Gradual Response Model. Also investigated the Differential Functioning of Items (DIF) for age, sex and presence of diseases. Results: (1) The pre-test suggested the incorporation of two new items and a focal group was conducted that, from the content analysis, generated the matrix of four sensory nodes. (2) The items presented good quality, adequate reliability (a Cronbach = 0.97) and reproducibility (ICC = 0.82). No significant impact DIF was detected. Conclusion: The translated pediatric version of PROMIS Upper Extremity Item Bank is an unprecedented, reliable and culturally appropriate evaluation measure to measure and monitor functional outcomes of clinical interventions aimed at manual dexterity.